MRI Pre‐ and Post‐Embolization Enhancement Patterns Predict Surgical Outcomes in Intracranial Meningiomas. Issue 1 (21st May 2015) - Ali, Rushna; Khan, Muhib; Chang, Victor; Narang, Jayant; Jain, Rajan; Marin, Horia; Rock, Jack; Kole, Max
ABSTRACT: PURPOSE: To evaluate the effects of preoperative embolization on overall surgical outcomes after meningioma resection and determine whether pre‐ and postembolization tumor enhancement patterns on magnetic resonance imaging (MRI) scans can be used to assess the efficacy of embolization. METHODS: We developed a prospective database of all patients who underwent surgical resection with or without preoperative embolization for extra‐axial intracranial meningiomas from 2004 to 2010. Using specialized computer software, the total volume of enhancement was calculated in pre‐ and postembolization MRI scans to quantify the percentage of embolization, which was described as the embolization fraction (EF). RESULTS: A total of 89 patients underwent surgical resection. Fifty two patients underwent embolization prior to surgery. Tumor location significantly correlated with the decision to embolize preoperatively. Adequate embolization was achieved in 58% of patients. Forty four patients (84.6%) had a postsurgical Karnofsky performance score (KPS) of 80 or above, while 46 patients (88.4%) had a postsurgical Glascow Outcome Score (GOS) of 4 or 5. The mean EF was 25.03% with a median of 18.72%. A greater extent of embolization as quantified by EF led to decreased intraoperative blood loss ( r = −.319, P = .022) and better postsurgical outcomes as defined by KPS ( r = .279, P = .044). CONCLUSIONS: Pre‐ and postembolization tumor enhancement patterns on magnetic resonance imaging defined as EF correlate with improved surgical facilitation and postoperative functional outcomes in the management of intracranial meningioma.